2012
DOI: 10.1111/j.1745-7599.2012.00766.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping behaviors used by Army wives during deployment separation and their perceived effectiveness

Abstract: Identifying effective and ineffective coping behaviors of spouses of deployed troops can potentially reduce stress and improve well-being. Primary care providers should encourage military spouses to engage in optimistic thinking, seek out spiritual support, talk to others in a similar situation, and participate in physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…Examining the use of problem-and emotion-focused coping, colleagues (2011a, 2011b) reported that coping styles were also related to various demographic variables such as the spouses and SMs' ages and the number of years on active duty. In general, younger spouses and SMs with less time on active duty used more evasive and emotional coping than confrontive coping methods (Blank, Adams, Kittelson, Connors, & Padden, 2012;Padden, 2011aPadden, , 2011b. One could stipulate that this is related to the lack of knowledge and experience with military resources and other resources.…”
Section: Research On Military Spousementioning
confidence: 94%
“…Examining the use of problem-and emotion-focused coping, colleagues (2011a, 2011b) reported that coping styles were also related to various demographic variables such as the spouses and SMs' ages and the number of years on active duty. In general, younger spouses and SMs with less time on active duty used more evasive and emotional coping than confrontive coping methods (Blank, Adams, Kittelson, Connors, & Padden, 2012;Padden, 2011aPadden, , 2011b. One could stipulate that this is related to the lack of knowledge and experience with military resources and other resources.…”
Section: Research On Military Spousementioning
confidence: 94%
“…Military wives are a vulnerable population that faces unique challenges related to the military way of life (Blank, Adams, Kittelson, Connors, & Padden, 2012). Work-related separation of families is becoming more common in our society.…”
Section: Significance To Nursing and Healthcarementioning
confidence: 99%
“…Many factors are associated with depression (e.g., medical conditions, substance abuse, mental illness), including stress. Depression occurs when effective coping mechanisms erode; and for many adults, the vicious cycle of stress becomes a recurring cause of depression (Black, 1993;Blank et al, 2012).…”
Section: Stress and Depressionmentioning
confidence: 99%
“…Factors that indicate a high risk for ineffective coping for spouses include young age, first time away from home, foreign born, and tenuous financial status (Stafford & Grady, ). Blank, Adams, Kittelson, Connors, and Padden () determined the most effective coping behaviors during deployment included optimistic thinking, seeking spiritual support, participation in physical activity, and speaking with other spouses support in a similar situation within a sample of Army spouses. It is imperative for healthcare providers, especially those working in primary care, to recognize the potential relationship between stressors within the military family, physical and psychological manifestations, and current coping behaviors as they relate to deployment.…”
Section: Implications For Nps In Primary Carementioning
confidence: 99%